Communication, relationships and care a reader - Robb, Martin; Robb, Martin; Open University (Routledge, 2004)
This reader provides a comprehensive collection of literature on communication, relationships and care. Its aim is to help people involved in care services as workers, carers or users to improve communication processes and develop more participatory relationships.
Keywords: Communication in social work; Communication in medicine; Communication in nursing; Interpersonal relations; Nurse and patient; Society; Social Change; Sociology & Social History; Social Sciences